Character education in English package books for Islamic Junior High School students - Wahyuningsih Usadiati; Maida Norahmi (Universitas Islam Negeri Palangka Raya, Indonesia, 2019)
The research is an inventory aimed at identifying and categorizing the character values in the English package books for students of Islamic Junior High School or Madrasah Tsanawiyah by considering their relevance to Islamic character values in the Quran and Hadits. The method used was content analysis following Bogdan and Biklen model by analyzing, grouping, sorting, and synthesizing the values taken from the package books to draw the patterns.